Verschil moet er zijn!: Naar een productieve spanning tussen godgeleerdheid en godsdienstwetenschappen - Boeve, Lieven (Tijdschrift voor theologie, 2008)
This essay introduces a cultural-theological perspective into the discussion on the relationship between theology and the study of religions. The author starts by reflecting on the way in which the Christian faith relates to the present context and the opportunities this offers for an authentic theological project. After defining several terms, the author starts from a perspective of the development of tradition as recontextualization to sketch a modern and post-modern background to the growing tension between theology and religious studies. Then he discusses two deficient strategies to defuse this tension. He considers the move from theology to religious studies and the increasing isolation and ‘pastoralising’ of theology to be inadequate responses to Christian faith’s changed relationship to the present context. The first appears to be a survival strategy after theology’s loss of cultural and scientific plausibility, while the second is a strategy to protect against the increased tension between faith/theology and context/sciences. Contrary to this, the author relies on an analysis of the context in terms of plurality and difference to argue for a theological project in which theology and religious sciences work together productively between continuity and discontinuity. Only thus can theology credibly assume its place at the intersection of church, academe and society. Finally, he puts this alternative into practice in four brief examples.